PEMANFAATAN ARANG AKTIF DARI AMPAS TEBU (Saccharum officinarum) PADA PEMURNIAN MINYAK GORENG BEKAS DENGAN METODE AKTIVASI KIMIA-FISIKA MENGGUNAKAN H3PO4 - Andri Gunawan Purba; Faizah Hamzah; Fajar Restuhadi. (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study was conducted experimentally by using Completely Randomized Design (CRD) with 4 treatments, namely AA1 (H3PO4 5%), AA2 (H3PO4 10%), AA3 (H3PO4 15%) and AA4 (H3PO4 20%) with 4 replications. Data obtained were analyzed statistically using Analysis of Variance (ANOVA) and if F count is greater than or equal to F table then continued with DNMRT test at 5% level. Observation was the physic chemical properties from the used cooking oil which includes  purified water content, free fatty acids, saponification, reduceperoxideand and organoleptic test (color and odor).The results showed interaction H3PO4 concentration significantly affect (P <0.05) the acquisition of free fatty acids, saponification and reduceperoxideand but did not significantly effect (P>0.05) the water content and organoleptic (color and smell). The results show that the higher the concentration of H3PO4 in the refining of used cooking oil significantly decreased the contents of free fatty acids, saponification,  reduceperoxideand and organoleptic test (color and odor) but increased saponification. It can be concluded that the best treatment was AA4 treatment (H3PO4 20%) with the content of purified water content 0.178%, free fatty acids 0.392%, saponification 180.98 mg KOH/g and greduceperoxideand 2.595 meq/g. Keyword: used cooking oil, refining used cooking oil, bagasse carbon